2018
DOI: 10.5430/cns.v6n2p79
|View full text |Cite
|
Sign up to set email alerts
|

The effect of self-care nursing intervention model on self-esteem and quality of life among burn patients

Abstract: Objective: Burn injuries and their complications are considered the major health problems throughout the world as it has a negative effect on function of the burned part that result in psychological disturbance as depression, anxiety, irritability, body image dissatisfaction and post-traumatic stress disorder are common in burn patients that associated with adverse out comes including poor quality of life (QOL), low self-esteem, stigmatization and increase mortality. This study aimed to investigate the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
4
10
0
Order By: Relevance
“…The percentage of area burned was observed to be between 10-25%. The previous findings are in agreement with Abd Elalem et al, (2018) [29] who stated that more than half of the studied patients had burns in different parts of the body rather than the face; also more than half of the patients had burns covering 10-25% of the body surface.…”
Section: Discussionsupporting
confidence: 92%
“…The percentage of area burned was observed to be between 10-25%. The previous findings are in agreement with Abd Elalem et al, (2018) [29] who stated that more than half of the studied patients had burns in different parts of the body rather than the face; also more than half of the patients had burns covering 10-25% of the body surface.…”
Section: Discussionsupporting
confidence: 92%
“…The results indicated that the scores of quality of life was with a significant increases at month three post-intervention. 10 The study by Elalem et al (2018) 3 demonstrated that self-care nursing was effective in burn patients and self-care intervention enabled patients to actively take part in their treatment. 3 Finlay et al performed a study in 2012 with the objective of developing and evaluating DVDbased self-care instructions for the burn outpatients and the findings of the present study are compliant with the aforesaid study, because the improvement in the physical performance scores was reflective of the effectiveness of multimedia self-care instruction.…”
Section: Discussionmentioning
confidence: 99%
“…10 The study by Elalem et al (2018) 3 demonstrated that self-care nursing was effective in burn patients and self-care intervention enabled patients to actively take part in their treatment. 3 Finlay et al performed a study in 2012 with the objective of developing and evaluating DVDbased self-care instructions for the burn outpatients and the findings of the present study are compliant with the aforesaid study, because the improvement in the physical performance scores was reflective of the effectiveness of multimedia self-care instruction. 26 As it is known, burns are chronic diseases that cause appearance changes, disabilities, difficulties in performing of the occupational duties and familial responsibilities as well as physical, psychological and social outcomes that can substantially influence quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations